Pendekatan Bayani, Irfani Dan Burhani Dalam Pengembangan Pembelajaran Pendidikan Agama Islam - Achmad Zuhri; Aulia Nisa Hanifa (Pascasarjana UIN Siber Syekh Nurjati Cirebon, 2026)
The purpose of writing this article is to describe the application of epistemology bayani and burhani in Islamic Religious Education (PAI) in madrasahs. The research method used is library research, which involves collecting data from literature, including several journal articles and books, followed by reading, noting, and processing the research materials. The results of this research indicate that the development of PAI learning, which is elaborated into four subjects Aqidah Akhlaq, Qur’an Hadith, Fiqh, and Islamic Cultural History begins with understanding the text of the learning material, which is in line with the concept of bayani reasoning. This is then followed by contextualizing the material using other sciences or with Burhan or signs of Allah's power, namely the universe. In this way, the learning process will achieve optimal results, aligning with the goal of Islamic education itself, which is to create individuals who are faithful, pious, and possess noble character. Keywords: Bayani, burhani, irfani, and PAI learning